DNA measurements and ploidy determination of developmental stages in the life cycles of Theileria annulata and T. parva - Gauer, M.; Mackenstedt, U.; Mehlhorn, H.; Schein, E.; Zapf, F.; Njenga, E.; Young, A.; Morzaria, S.P. (Springer, 1995)
The relative DNA levels of different development stages of Theileria annulata and T. parva in the cow and the tick were measured by the cytophotometric DNA technique using the fluorochrome Hoechst 33258 as a staining dye. The results revealed that sporozoites, merozoites, gamonts, and gametes were haploid, where-as multinucleated intralymphocytic schizonts were polyploid. No difference was observed between T. parva and T. annulata in these stages. For both Theileria species, the DNA measurements revealed that fusion of gametes occurred in the gut of the final host, thus providing evidence of sexual reproduction. However, differences were observed between the two parasites in the tick. Whereas T. parva zygotes underwent a two-step meiotic division, a comparable reduction division could not be unequivocally detected in T. annulata. Differences could also be detected in the further development of kinetes, indicating that Theileria species are not characterized by only one life cycle, which is specific for this genus.